PARENTS AND TEACHERS OPINIONS ON INCLUSIVE PRACTICES IN A SECONDARY SCHOOL, TAIPING DISTRICT.PERAK.MALAYSIA (Proceedings of International Conference on Special Education, 2015)
Inclusive philosophy has its own power in the process of "normalization" of children with special needs. This study discusses the perceptions of inclusive education in a school. It is a case study to explore the opinion of regular teachers and parents towards inclusive practice. The research method is through individual interviews with regular teachers, special educators and the parents of the special student. The findings show that regular teachers and special educators maintain their roles and responsibilities, while parents and teachers have a positive outlook on the learning outcomes in terms of social development and integration. Discussions were focus on reforming education practices and strategies for collaboration and sharing of tasks among teachers to promote an inclusive environment in school.